Delineating Binding Modes of Gal/GalNAc and Structural Elements of the Molecular Recognition of Tumor‐Associated Mucin Glycopeptides by the Human Macrophage Galactose‐Type Lectin. Issue 49 (16th October 2014) - Marcelo, Filipa; Garcia‐Martin, Fayna; Matsushita, Takahiko; Sardinha, João; Coelho, Helena; Oude‐Vrielink, Anneloes; Koller, Christiane; André, Sabine; Cabrita, Eurico J.; Gabius, Hans‐Joachim; Nishimura, Shin‐Ichiro; Jiménez‐Barbero, Jesús; et al.
Abstract The human macrophage galactose‐type lectin (MGL) is a key physiological receptor for the carcinoma‐associated Tn antigen (GalNAc‐α‐1‐O‐Ser/Thr) in mucins. NMR and modeling‐based data on the molecular recognition features of synthetic Tn‐bearing glycopeptides by MGL are presented. Cognate epitopes on the sugar and matching key amino acids involved in the interaction were identified by saturation transfer difference (STD) NMR spectroscopy. Only the amino acids close to the glycosylation site in the peptides are involved in lectin contact. Moreover, control experiments with non‐glycosylated MUC1 peptides unequivocally showed that the sugar residue is essential for MGL binding, as is Ca2+. NMR data were complemented with molecular dynamics simulations and Corcema‐ST to establish a 3D view on the molecular recognition process between Gal, GalNAc, and the Tn‐presenting glycopeptides and MGL. Gal and GalNAc have a dual binding mode with opposite trend of the main interaction pattern and the differences in affinity can be explained by additional hydrogen bonds and CH–π contacts involving exclusively the NHAc moiety.